Pengaruh Model Pembelajaran Contextual Teaching And Learning (Ctl) Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPA Kelas IV SD Negeri 6 Kendari - Hasriani Hasriani; Kasmawati Kasmawati; Arna Juwairiyah (Jurnal Kajian Pendidikan dan Cakrawala Pembelajaran, 2025)
This research is motivated by the lack of application of learning innovative in elementary schools. This results is low student achievement, especially in science subjects. The purpose of this research is to describe the influence of the contextual teaching and learning (CTL) learning model on student learning outcomes in grade IV science subjects. The type of research used in this research is quasy experiment, or quasy experiment with a pretest-posttest control group design. Based on on the results of research conducted, it shows that the results of the paired sample test (paired t-test) obtained a sig (2-tailed) value of 0,000 < 0,05 indicating that there is a significant difference between the experimental class and the control class. So it can be concluded that by using the contextual teaching and learning (CTL) influences student learning outcomes in class IV science subjects at at Kendari 6 Public Elementary School.